2009
DOI: 10.1111/j.1540-6210.2009.02110.x
|View full text |Cite
|
Sign up to set email alerts
|

Private Sector Imprinting: An Examination of the Impacts of Private Sector Job Experience on Public Manager's Work Attitudes

Abstract: What are the attitudes of public managers who have had full-time private sector work experience? Public managers with private sector work experience report diff erent perspectives when compared to their counterparts who have spent their entire careers in the public sector. Th ough private sector work experience negatively correlates with job satisfaction, it only does so for the "new switcher," whose last job was in the private sector. As careers advance, the negative impact seems to wane, leaving a public sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 72 publications
2
67
0
Order By: Relevance
“…This suggests that previous job or sector experience shape the attitudes of employees toward work and their communities. Boardman et al (2010) also found previous work experience has an impact on job satisfaction and job involvement for individuals who switched from the private to the public sector. According to them, individuals who previously worked in the private sector are more involved in their jobs than those who have no private sector experience.…”
Section: Previous Sector Job Experiencesmentioning
confidence: 83%
“…This suggests that previous job or sector experience shape the attitudes of employees toward work and their communities. Boardman et al (2010) also found previous work experience has an impact on job satisfaction and job involvement for individuals who switched from the private to the public sector. According to them, individuals who previously worked in the private sector are more involved in their jobs than those who have no private sector experience.…”
Section: Previous Sector Job Experiencesmentioning
confidence: 83%
“…Nonprofits represent the fastest-growing sector of the U.S. economy (Wing, Pollak, and Blackwood 2008), and these organizations continue to take on a larger role in delivering services in the United States. Moreover, as more managers engage in sector switching (Boardman, Bozeman, and Ponomariov 2010;Feeney 2008), the context of the work environment might play an increasingly important role in attracting and retaining talent over the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in applied and occupational psychology suggest that transitioning to a job that expects roles and behaviors that are different from prior work experiences can affect attitudes toward one’s current job (Louis 1980; West and Rushton 1989). Past career experiences have been shown to play a role in the formation of both positive and negative attitudes and perceptions (Petty and Krosnick 1995; Songer‐Nocks 1976), including the work attitudes of public managers (Boardman, Bozeman, and Ponomariov 2010). Studies of workplace socialization additionally have suggested that work attitudes and perceptions are, in part, a function of the length of tenure in past jobs (Reichers, Wanous, and Steele 1994).…”
Section: Theory and Hypothesesmentioning
confidence: 99%